The Influence of Customer Trust On Customer Loyalty in Doing Online Shopping Through Shopee - Aisya Salsabila Benta; Budi Astuti (Cita Konsultindo Research Center, 2024)
The purpose of this study is to analyze the relationship between customer trust and customer loyalty in doing online shopping through the Shopee website which is supported by how the quality and design of the website affect the relationship between the two. The methodology used in this research is a quantitative approach with non-probability sampling techniques. The criteria for respondents in this study are aged 17 years and over and have purchased products through Shopee. The number of valid respondents was 175. Data processing using the PLS-SEM method. The variables used in this study are service quality, website quality, information quality, reliability, perceived security, perceived usefulness, customer trust and customer loyalty. The results of this study indicate that website quality, information quality, security and perceived usefulness have a positive effect on customer trust. Customer trust has a positive effect on customer loyalty. Meanwhile, service quality and reliability have no effect on customer trust. The results of this thesis research are expected to help marketers and companies develop more intimate relationships with customers and encourage customer loyalty through customer trust.